Nepal’s Performance in Achieving Sustainable Development Goals: A Critical Evaluation - Pant, Ram Kumar (Kaumodaki: Journal of Multidisciplinary Studies, 2024)
This study focuses on the agenda of UN conference to be achieved by 2030. The main objective of the study is to assess the sustainable development goals achieved by Nepal in different points of time and its work progress made by Nepal. Based on the qualitative as well as descriptive method, this study explores the localization of sustainable development goals in the context of Nepal. It has found out 17 goals, out of which Nepal has made high performance in goals 5, 12 and 13 and doing satisfactory progress in other goals like 4, 6 and 1, respectively. However, the country is surpassing through the difficult situations in order to achieve the goals by the timeframe. Nepal has added more indicators to localize sustainable development goals in the context of the country. The post covid-19, natural disaster and nation’s internal political instability, political commitment and insufficient resources are considered hindrances in achieving the declared goals.